1993
DOI: 10.2307/2992465
|View full text |Cite
|
Sign up to set email alerts
|

The Origin and Evolution of Parthenogenesis in Heteronotia binoei (Gekkonidae): Reciprocal Origins and Diverse Mitochondrial DNA in Western Populations

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.Abstract.?Parthenogenetic lines of the Heteronotia binoei complex are genetically diverse, of hybrid origin, and geographically widespread, ranging from central Australia to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Based on the mtDNA restriction profiles showing an affinity of 3N2 mtDNA with a clade of SM6 haplotypes from the extreme western part of their range along the northwest coast of Australia, Moritz and Heideman [27] concluded that the 3N2 mtDNA lineage had likely originated in the northwestern part of its range (see Figure 2 in 26). Under this scenario, 3N2 parthenogens then spread to the east and south to occupy their current range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the mtDNA restriction profiles showing an affinity of 3N2 mtDNA with a clade of SM6 haplotypes from the extreme western part of their range along the northwest coast of Australia, Moritz and Heideman [27] concluded that the 3N2 mtDNA lineage had likely originated in the northwestern part of its range (see Figure 2 in 26). Under this scenario, 3N2 parthenogens then spread to the east and south to occupy their current range.…”
Section: Discussionmentioning
confidence: 99%
“…Heteronotia binoei is a complex of several diploid sexual chromosome races and two mitochondrially distinct lineages of triploid parthenogenetic clones that formed via hybridization between two of the sexual chromosome races [26]. The CA6 and SM6 sexual chromosome races were involved in reciprocal hybridization events giving rise to the 3N1 and 3N2 (so named because they are triploid) parthenogenetic mtDNA lineages [27]. A third sexual chromosome race, EA6, was not involved in the hybridization events but is geographically widespread and sympatric with 3N1 parthenogens in part of its range.…”
Section: Introductionmentioning
confidence: 99%
“…Since mtDNA is maternally inherited, it is also a suitable tool to identify the maternal ancestors of hybrid parthenogens [16-20]. Both allow identification of the rate at which new parthenogenetic lineages arise, and to what extent the presence of sexual conspecifics is required.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent surveys revealed that the parthenogens are very widely distributed in the central and western deserts, occurring over an area in excess of 1.5 X 106 km 2 (Fig. Genetic diversity in the parthenogens has now been analysed from several perspectives -chromosomes (Moritz, 1984;Moritz et al, 1989a), allozymes (Moritz et al 1989b), ribosomal RNA genes (rRNA, Hillis et al, 1991), and mitochondrial DNA (mtDNA, Moritz, 1991;Moritz & Heideman, 1993) -revealing a rich panoply of variation (Table 1). Genetic diversity in the parthenogens has now been analysed from several perspectives -chromosomes (Moritz, 1984;Moritz et al, 1989a), allozymes (Moritz et al 1989b), ribosomal RNA genes (rRNA, Hillis et al, 1991), and mitochondrial DNA (mtDNA, Moritz, 1991;Moritz & Heideman, 1993) -revealing a rich panoply of variation (Table 1).…”
Section: Extent and Source Of Genetic Diversity Of Parthenogenetic Hmentioning
confidence: 99%
“…Restriction analysis revealed two assemblages of mtDNAs from the parthenogens that differed by about 12% of sequence and which had largely discrete geographic distributions (Moritz, 1991;Moritz & Heideman, 1993). Restriction analysis revealed two assemblages of mtDNAs from the parthenogens that differed by about 12% of sequence and which had largely discrete geographic distributions (Moritz, 1991;Moritz & Heideman, 1993).…”
Section: The Mode and Dynamics Of Origin: Evidence From Mtdnamentioning
confidence: 99%